Intersections and Multiple 'Candidacies': Exploring Connections between Two Theoretical Perspectives on Domestic Abuse and Their Implications for Practicing Policy. Issue 1 (24th June 2014) - Mackenzie, Mhairi; Conway, Ellie; Hastings, Annette; Munro, Moira; O'Donnell, Catherine A.
Abstract : Domestic abuse policy increasingly uses language which indicates that abuse is patterned according to structural factors. However, practicing according to these structural accounts of abuse is problematic because of the policy and organisational contexts that practitioners work within and, we argue, because the implications of the structured nature of victims' experiences is not fully understood by all practitioners. We ask whether women's differential use and experiences of services with a remit to address abuse can be illuminated using two theoretical perspectives – 'candidacy' and intersectionality. We report the findings of a literature synthesis that investigates how these improve our understanding of women's help-seeking and service utilisation and of the responses that they receive. Both concepts were highly congruent with the literature and we conclude that, together, candidacy and intersectionality offer a means of enhancing knowledge of how the political becomes enacted in the personal. Embedding such knowledge within practice repertoires offers the potential to develop more nuanced structural understandings of women's experiences and constraints.